Defending jacob ebook A novel. - Landay, William (2012)
NEW YORK TIMES  BESTSELLER • “A legal thriller that’s comparable to classics such as Scott Turow’s  Presumed Innocent  . . . tragic and shocking.”—Associated Press NOW AN EMMY-NOMINATED ORIGINAL STREAMING SERIES • NAMED ONE OF THE BEST BOOKS OF THE YEAR BY  Entertainment Weekly  •  Boston Globe  •  Kansas City Star Andy Barber has been an assistant district attorney for two decades. He is respected. Admired in the courtroom. Happy at home with the loves of his life: his wife, Laurie, and their teenage son, Jacob. Then Andy’s quiet suburb is stunned by a shocking crime: a young boy stabbed to death in a leafy park. And an even greater shock: The accused is Andy’s own son—shy, awkward, mysterious Jacob. Andy believes in Jacob’s innocence. Any parent would. But the pressure mounts. Damning evidence. Doubt. A faltering marriage. The neighbors’ contempt. A murder trial that threatens to obliterate Andy’s family. It is the ultimate test for any parent: How far would you go to protect your child? It is a test of devotion. A test of how well a parent can know a child. For Andy Barber, a man with an iron will and a dark secret, it is a test of guilt and innocence in the deepest sense. How far would  you  go? Praise for Defending Jacob “A novel like this comes along maybe once a decade . . . a tour de force, a full-blooded legal thriller about a murder trial and the way it shatters a family. With its relentless suspense, its mesmerizing prose, and a shocking twist at the end, it’s every bit as good as Scott Turow’s great  Presumed Innocent . But it’s also something more: an indelible domestic drama that calls to mind  Ordinary People  and  We Need to Talk About Kevin . A spellbinding and unforgettable literary crime novel.” —Joseph Finder “ Defending Jacob  is smart, sophisticated, and suspenseful—capturing both the complexity and stunning fragility of family life.” —Lee Child “Powerful . . . leaves you gasping breathlessly at each shocking revelation.” —Lisa Gardner “Disturbing, complex, and gripping,  Defending Jacob  is impossible to put down. William Landay is a stunning talent.” —Carla Neggers “Riveting, suspenseful, and emotionally searing.” —Linwood Barclay